Analysis of cooling load calculations using AHU in swimming pools (indoor pools) - M. Sugiri; Indra Widarmadi; Parman Sinaga; Wahyudi (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
AC or Air Conditioner is one of the most widely used mechanical devices in Indonesia. A machine device that functions as an air conditioner so that the indoor air temperature is comfortable, healthy, and has the humidity required by the occupants. Air freshening systems or ACs are increasingly becoming a necessity for urban communities, whether in homes, office buildings, apartments, hotels, swimming pools, hospitals, and even in lecture rooms. The indoor swimming pool measuring 40 x 11 x 3.5 m is located in the apartment So it is uncomfortable for swimmers. Thus, it is necessary to design using an AC system so that the temperature in the swimming pool is cool and comfortable for swimmers. The planning methodology starts by determining data on the indoor swimming pool in apartment AC used. From the analysis results, the cooling load was obtained at 411.5 kW, including a sensible load of 397.66 kW and a Latin load of 13.85 kW, the refrigerant used by the engine was R134a, the compressor power was 81 HP, while the COP was 6.8. So that the indoor air is evenly distributed comfortably, the indoor cold air distribution system uses an AHU (Air Handling Unit) system, capacity of 1900 m3/hour. 2 AHU Units, Blower Power 3 kW